DEVELOPMENT OF AN ECOLITERACY-BASED E-LKPD USING LIVEWORKSHEETS ON ENVIRONMENTAL CHANGE MATERIALS FOR GRADE X - Faiz Reihan Irfan; Yustina; Nursal (Yayasan Amanah Nur Aman, 2026)
This study was motivated by the low utilization of contextual digital teaching materials in learning environmental change topics, resulting in environmental awareness and students’ critical thinking skills not developing optimally. The study aimed to develop an ecoliteracy-based E-LKPD using Liveworksheets on environmental change materials for Grade X and to describe its validity and practicality levels. The research employed a Research and Development approach using the ADDIE model, limited to the analysis, design, and development stages. Data were obtained through teacher interviews, validation by subject-matter and media experts, and a small-group trial involving 15 students of SMA IT Fadhilah Pekanbaru using a Likert-scale questionnaire. The validation results showed an average score of 79% (valid category) for the material, media, and language aspects, while practitioner (teacher) validation reached 90% (very valid category). The student practicality trial produced an average of 91.5% in the very practical category, viewed from a systematic instructional design, ease of operation, and an attractive and contextual appearance. The integration of cognitive, attitudinal, and skills aspects within the ecoliteracy framework encourages students to analyze environmental problems, develop ecological empathy, and demonstrate responsibility toward the environment. It is concluded that the developed ecoliteracy-based E-LKPD is valid and highly practical for use as an alternative digital teaching material to support the implementation of the Merdeka Curriculum and the strengthening of the environmentally oriented Pancasila Student Profile.